(untitled) - Vigor, John (Camden, Me., 2004)
The Practical Encyclopedia of Boating is the first guide to all practicaland many theoreticalaspects of recreational boating under sail and power. From seamanship to maintenance, navigation to boat design and construction, nautical lore and esoterica to the science of how things work, this handy reference gives sailors and powerboaters quick access to just the right amount of information needed to answer most questions and solve most problems.
Keywords: Boats and boating,Tàu thuyền và du lịch trên thuyền